Analysis of Providing Protection to Children Who Are Victims of Sexual Violence - Vincentius Patria Setyawan (Publikasi Inspirasi Indonesia, 2024)
A crime that has been occurring recently and is a matter of concern is sexual violence. It is even more worrying because the majority of those who are victims of sexual violence are children. Children as the nation's next generation should receive protection in the process of their growth and development to become a superior generation. In this regard, it is important to analyze the regulations for providing protection for children who are victims of sexual violence. This research uses normative legal research methods with a conceptual approach. The results of this research are that the forms of legal protection that children who are victims of sexual violence need are legal assistance, rehabilitation, health services and social security in accordance with their physical, mental, spiritual and social needs. The obstacles that occur in providing protection to child victims of sexual violence can be classified as structural obstacles, substance obstacles, cultural obstacles, and infrastructure obstacles.